Comparison of QFT-IT and QFT-Plus for Detecting Latent Tuberculosis in HIV-Infected Iranian Patients - Zahra Abtahian; Elaheh Eghbal; Payam Tabarsi; Farima Khalili; Mohammad Javad Nasiri (Novelty in Biomedicine, 2025)
Background: Tuberculosis (TB) is a major public health issue, especially among Human immunodeficiency virus (HIV)-infected individuals, where early detection of latent tuberculosis infection (LTBI) is crucial. Interferon-gamma release assays (IGRAs), like quantiferon-TB gold "in tube" (QFT-IT) and QFT-Plus, are more accurate alternatives to the tuberculin skin test (TST). This study compares the diagnostic performance of QFT-IT and QFT-Plus for detecting LTBI in HIV patients in Iran.